Determinants of the Intentions of Indonesian Muslim Millennials in Cash Waqf Using E-Payment - Ucu Musahidah; Nurdin Sobari (Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to explain the factors that influence the intention of Indonesian Muslim millennials in paying cash waqf using e-payment. This study uses the UTAUT theory where Religious Belief, Level of Knowledge, and Image are added to the main components. As well as testing the Effort Expectancy variable as a moderator between Performance Expectancy and Behavioral Intention. This research was conducted through an online survey involving 310 respondents who have never had cash waqf. Quantitative analysis based on PLS-SEM shows that Performance Expectancy, Effort Expectancy, Social Influence, Level of Knowledge, and Image variables significantly affect the millennial generation's intention in paying cash waqf using e-payment. However, the variables Facilitating Condition and Religious Belief were found to be insignificant, as well as Effort Expectancy as a variable moderator between Performance Expectancy and Behavioral Intention was found to be insignificant on the millennial generation's intention in paying cash waqf using e-payment.